Attitudes Toward Marriage and Gender Roles as Predictors of Parenting Sense of Competence in Unmarried Early Adulthood - Annisa, Nida Muthi; Limin, Debby Sutanti; Widhyastuti, Cahyaning; Putri, Pradiptya S (Research Collaboration Community (Rescollacom), 2025)
This study aims to examine attitudes toward marriage (ATM) and gender roles as predictors of parenting sense of competence (PSOC) among unmarried individuals in early adulthood. A quantitative approach was employed using multiple linear regression analysis. The participants consisted of 97 unmarried early adults. The results showed that attitudes toward marriage (MAS) and gender role attitude (GRA) significantly predicted parenting sense of competence (F(2,94) = 6.272, p = .003). The coefficient of determination (R²) was .118, indicating that the two independent variables accounted for 11.8% of the variance in PSOC. Although the predictive contribution is relatively low, the findings suggest that attitudes toward marriage and gender roles are meaningful factors in shaping parenting competence, even among individuals without direct parenting experience. These results provide valuable insights for educational interventions and parenting preparation programs targeting early adulthood populations.